Plan de mejoramiento institucional como dispositivo de gestión participativa para el fortalecimiento de la calidad educativa (2014)
This research aims to establish the incidence of Institutional Improvement Plan (PMI) as device management, strengthening the quality of education from the collective construction. This exercise focused on the implementation of educational action research with two phases (diagnostic and interventional); Group 4 participant taking as public educational establishments Barranquilla, under some institutional criteria of the District Government. Record instruments such as characterization, two sessions of group discussions, workshops and support in situ by the research group were administered. The results show that the PMI is poorly understood and conceived more as a delivery requirement to territorial entity. While in Phase II, the meaning of this instrument changes and redefined in the participating Member, conceptual schemes and organizational culture in the context of the relevance, development, evaluation and participation.